Spectrophotometric Studies on Cobalt(II) Complex of 4-Methyl Dibenzoylmethane - C. Sharma, Subhash; Tyagi, M.P. (Asian Journal of Chemistry, 2010)
4-Methyl dibenzoylmethane forms 1 : 1 (M : R) yellow complex with Co(II) at pH 8.0 to 8.9 Working wavelength used for spectrophotometric study of the complex is 390 nm. Values of λ-maxima, molar absorptivity 'ε', sandell's sensitivity, stability constant (log K) and free energy of formation (ΔF) were found to be 385 nm, 8000 cm–1 mol–1, 0.0073 μg cm–2, 4.675 and –6.376 k.cals per mole respectively. Beer's law is obeyed in concentration range of 1×10–5 –6×10–5M.